PEMANFAATAN LIMBAH MINYAK BEKAS PENGGORENGAN TAHU SEBAGAI BAHAN DASAR PEMBUATAN BIODIESEL - De Budi Irwan Taufik (Jurnal Life Science : Jurnal Pendidikan dan Ilmu Pengetahuan Alam, 2019)
AbstractThis research is entitled “Utilization of “tofu/ soybean curd” used oil waste as a basic of biodiesel making”. This research aims to “Find out whether the used frying oil can be used as a base for biodiesel, and how is the quality of the biodiesel produced?". The oil used in this study is new and used palm oil commonly used as an ingredient for frying tofu obtained from 4 (four) tofu factories in the Karacak area of Garut Regency. Making biodiesel uses the method put forward by Mike Pelly found in Mike's method in Spanish: Formula de Mike Pelly (Mike Pelly, 2003: February 24). Furthermore, testing is carried out on Specific Gravity, Thickness (Kinematic Viscosity 400C, mm2 / s), Flash point (Flash Point, 0F), and Calculated Rate (Index Calculated Index). The processing technique used for this study is the F Test and the t Test. From the four data tested, the results obtained are Fcount <Ftable, which means the variation of the two samples is homogeneous. From processing data with t test, the results obtained where tcount < ttabie, which means that between biodiesel from used oil is not significantly different from biodiesel from new oil. So that from the results of research and discussion, it was concluded that the frying oil used in Transesterification reactions can produce Biodiesel that meets the ASTM Standard and can be used as an alternative energy source for diesel.Keywords: Utilization, Waste, Basic Materials, Biodiesel